2004
DOI: 10.1002/micr.20026
|View full text |Cite
|
Sign up to set email alerts
|

Effect of the two‐wall‐stitch mistake upon patency of rat femoral vein anastomosis: Preliminary observations

Abstract: Anastomotic patency is believed to be the most important factor in microvascular surgery. The two-wall stitch is a technical error commonly considered to cause thrombosis of the anastomosis, especially on the venous side. In order to demonstrate the real effect on vein patency of the two-wall stitch, the authors performed a standardized mistake after correct microanastomosis on the femoral vein of 15 rats, with one stitch passing through the whole thickness of the two walls of the vein. Traditional correct ana… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
14
0

Year Published

2008
2008
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 9 publications
(14 citation statements)
references
References 10 publications
0
14
0
Order By: Relevance
“…In our experimental study, apart from providing enough statistical power, we tried to decrease confounding factors to isolate the relations between anastomotic patency, which is believed to be the most important factor in microvascular surgery, 31,42,45,46,48,49 and radiotherapy. Thus, we did not opt for an irradiation model over a flap’s pedicle but a model of 2 independent vessels in the same surgical field approached by a single incision.…”
Section: Discussionmentioning
confidence: 99%
“…In our experimental study, apart from providing enough statistical power, we tried to decrease confounding factors to isolate the relations between anastomotic patency, which is believed to be the most important factor in microvascular surgery, 31,42,45,46,48,49 and radiotherapy. Thus, we did not opt for an irradiation model over a flap’s pedicle but a model of 2 independent vessels in the same surgical field approached by a single incision.…”
Section: Discussionmentioning
confidence: 99%
“…The milking test subjectively revealed the occlusion of the vessel lumen and is related to the degree of anastomotic vessel constriction caused by thrombosis and affected mainly by the surgeon's skill. 13,24 Results of early and late milking tests were not compromised in any of the anastomoses (p > 0.05; Table 2). In terms of quality of filling, however, C suture technique was inferior compared with the other suture techniques.…”
Section: Anastomotic Leakage and Patencymentioning
confidence: 92%
“…6 Success of microvascular anastomosis and minimization of postoperative complications are related to exposition of adventitia and media 7 ; choice of suture material and needle 8 ; number of sutures 9 ; suturing technique 1,10 ; elimination of luminal occlusion linked to inversion, eversion, stenosis, thrombosis, and intimal thickening 11 ; and freeing the lumen from foreign material 12 as well as atraumatic meticulous handling. 2,13 In earlier literature, the continuous (C) suture technique has been favored due to the speed of execution and visualization of the lumen. 14,15 However, due to the luminal constriction, anastomosis by C suturing technique may lead to stenosis.…”
mentioning
confidence: 99%
“…3 The milking test is the most commonly performed method used for intraoperative assessment of anastomotic patency which is easy to perform and gives the surgeon the opportunity to control the blood stream under direct vision. 4 This test is performed a few centimeters distal to the anastomosis. 5 However, the study of Petry et al showed that milking test causes endothelial cell loss and thus increases the risk of anastomotic failure.…”
mentioning
confidence: 99%